Introduction to Special Issue: Integrating Technology Within Classroom Practices. (January 2017) - Musti-Rao, Shobana
The purpose of this special issue to provide teachers with ideas and resources on how to integrate technology into evidence-based practices in their classroom. The articles featured in this special issue focus on teaching academic and behavioral skills that can be implemented within a tier-based instructional framework (e.g., response to intervention) for students struggling to meet grade-level requirements in inclusive settings.